Стратешки пристап кон локалниот економски развој - случајот на општина Ресен - Рунчевска, Биљана (Економски факултет, УКИМ, Скопје, 2017)
The local economical development (LED) presents a positive challenge for the local authorities. It can be presented as creating and implementing activities and measures previously embedded in the Strategy. In the Strategy’s preparation are actively involved all interested participants who are trying to use the available local resources in their best way in order to achieve the desired future that will bring better economic conditions for the local population. The strategic approach towards the LED helps the local authorities to see where they are, where they want to go and how to get there. In the contemporary circumstances the local communities have undelayed needs to approach towards strategic planning. One of the municipalities in the R. Macedonia which is planning the activities of the jurisdiction for the local economic development through bringing strategy for the LED, presents the municipality of Resen. The municipality of Resen has developed and realized Strategy for the LED for the period from 2007 to 2012 year, and the new strategy is developed and refers to the period from 2016 to 2021 year. In the process of strategic planning of the municipality of Resen it can be identified the key steps that are indicated in the theory, and are applied in the practice in the other municipalities. Through the strategic approach towards LED, the municipality of Resen identifies and determines its needs, priorities, aims and tasks that are supported with by a project. And by doing so the municipality is focused towards the implementation of a new strategy for the LED. According to the department of LED of the Resen municipality, the new strategy refers to the period from 2016 to 2021 year. In the previous 2-3 decades, the local economy of the municipality of Resen it was heavily influenced by the transition process. Large is the number of the companies that have stopped their business activities. In the context of strategic approach towards the LED, the municipality of Resen needs measures and activities that will contribute improving the local economy. Therefore the recommendations for the further strategic approach towards the LED can contribute for better and more successful strategic plan for the LED of the municipality of Resen with which is realistic to be expected improvement of the economic future of this municipality.
Strategic approach toward local economic development - case study of Resen municipality
Докторска дисертација одбранета во 2017 година на Економскиот факултет во Скопје, под менторство на проф. д–р Пеце Недановски.
Keywords: local economic development, strategy, strategic planning, municipality of Resen, perspectives of LED